THE EFFECT OF USING THINK -TALK -WRITE STRATEGY ON THE ELEVENTH GRADE STUDENTS' ABILITY IN WRITING RECOUNT TEXT AT SMKS 2 TAMAN SISWA PEMATANG SIANTAR - Angelina Sinabutar; Selviana Napitulu; Bernieke Anggita Ristia Damanik (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This research was carried out to find out the effect of the Think-Talk-Write Strategy on students' ability in writing generetic structure recount text at eleventh grade of SMK 2 Taman Siswa Pematangsiantar. The research methodology used in this research was a quantitative method. The population of this research was eleventh grade at SMKS 2 Taman Siswa Pematangsiantar in the academic year 2025/2026. The researcher took two classes as the sample. The samples were XI TKR-1 as an experimental group consisting of 30 students and XI TKR -2 as a control group consisting of 30 students. The data were obtained by using the pre-test and post-test given to both groups. The experimental class mean score on the pre-test was 62, and the mean score of the control class was 68,2. On the other hand, the mean score of the experimental class on the post-test was 84,5, while the mean score of the control class on the post-test was 79,4. To acquire data, the researcher used a test as an instrument. The result of the t-test was 3,501, which was higher than the t-table at 5% level of significance (1,672). The result of significance value indicates that alternative hypothesis (Ha) was accepted, while the null hypothesis (Ho) was rejected. It meant that there was a significant effect by using the Think-Talk-Write Strategy at eleventh grade of SMKS Taman Siswa Pematangsiantar in writing recount text.